Evaluation of the local employment impacts of enterprise zones: A critique. (August 2019) - Chaudhary, Nidhi; Potter, Jonathan
Enterprise zone policy is a potential tool for the regeneration of distressed areas, based primarily on tax incentives to businesses locating in the target areas. The tool has been tested in several countries over more than 35 years but there is no consensus on whether or not it is effective and efficient in creating jobs and reducing unemployment in targeted localities. This paper reviews seminal enterprise zone evaluations in the UK, USA and France. More than one-half of the studies reported local employment benefits but the others reported none and information is limited on what affects policy success. The paper argues that typically narrow-focus research designs and a-theoretical evaluation have contributed to the lack of consensus and policy insight, potentially exacerbated by non-exact data. It proposes richer evaluations with explicit theoretical frameworks, such as the one presented in the paper, more comparative work and the use of more accurate data.